The Impact of Ippunkan Supīchi on Japanese Conversation Skills: Cognitive and Affective Outcomes Perceived by Universitas Andalas Japanese Students - Devi, Rima; Putri, Darni Enzimar; Idrus, Idrus (Andalas International Journal of Socio-Humanities, 2025)
Japanese language learners at Universitas Andalas face significant challenges in achieving oral proficiency, particularly spontaneous speaking fluency and confidence. To address this, the present study investigates the implementation of the ippunkan supīchi (one-minute speech) method in Japanese kaiwa (conversation) courses. This quantitative and qualitative study utilized a questionnaire to evaluate student perceptions across ten key indicators of speaking competence, administered to 34 Japanese literature students who practiced weekly one-minute speeches for seven consecutive weeks. Results demonstrated unanimous improvement in confidence and spontaneous speaking ability (100%), with 85.3%–94.1% of participants reporting enhanced vocabulary retention, grammatical accuracy, reduced speaking anxiety, and faster response times. The findings substantiate the method's efficacy in fostering cognitive processing efficiency (e.g., lexical retrieval) and affective outcomes (e.g., self-efficacy) in L2 Japanese speakers. This study contributes empirical evidence for task-based language teaching approaches that combine time constraints with repetitive practice to optimize speaking proficiency.